Կառավարչական գործունեության ազդեցությունը անձի հոգեբանական հատկությունների ձևավորման վրա - Արսեն Լոքյան (ՀՀ ԳԱԱ հրատ.)
In the article the influence of managerial activity on the forming a person's psychological features is handled. The social environment plays a significant role in the process of an individual's formation.
Keywords: Psychology